Measuring selective mutism disorder among primary school students (Journal of the College of Basic Education, 2022)
The current research aims to build a measure of selective silence disorder and to know the rates of prevalence of selective silence disorder among first-grade students from the primary stage, and to know the differences in selective silence disorder according to the gender variable (male-female). The research sample consisted of (500) students distributed according to The gender variable, with (250) males and (250) females studying in Baghdad governorate schools. The selective mutism scale was prepared by following scientific procedures. The results showed that students with Selective Mutism constituted (13%) of the sample, while there were no statistically significant differences between males and females in Selective Mutism Disorder.